Numerical simulation of enhancing coalbed methane recovery by injecting CO2 with heat injection - Hui-Huang Fang (KeAi Communications Co., Ltd., 2019)
Abstract The technology used to enhance coalbed methane (CBM) recovery by injecting CO2 (CO2-ECBM) with heat, combining heat injection with CO2 injection, is still in its infancy; therefore, theoretical studies of this CO2-ECBM technology should be perused. First, the coupling equations of the diffusion–adsorption–seepage–heat transfer fields of gas are established. The displacement processes under different pressures and temperatures are simulated by COMSOL. Finally, the displacement effects, a comparison of the CO2 storage capacity with the CH4 output and the effective influencing radius of CO2 injection are analyzed and discussed. The results show that (1) the displacement pressure and temperature are two key factors influencing the CH4 output and the CO2 storage capacity, and the increase in the CO2 storage capacity is more sensitive to temperature and pressure than the CH4 output. (2) The gas flow direction is from the injection hole to the discharge hole during the displacement process, and the regions with high velocity are concentrated at the injection hole and the discharge hole. (3) A reduction in the CH4 concentration and an increase in the CO2 concentration are obvious during the displacement process. (4) The effective influencing radius of injecting CO2 with heat increases with the increase in time and pressure. The relationship between the effective influencing radius and the injection time of CO2 has a power exponential function, and there is a linear relationship between the functional coefficient and the injection pressure of CO2. This numerical simulation study on enhancing CBM recovery by injecting CO2 with heat can further promote the implementation of CO2-ECBM project in deep coal seams.